School teaching literature in the period of reconstruction and improvement of the Sovietmodel of education in the USSR (1944–50’s) (Pedagogy of Higher and Secondary Education, 2013)
Josan O. E. School teaching literature in the period of reconstruction and improvement of the Sovietmodel of education in the USSR (1944–50’s).In the article we analyze the status and trends of school educational literature in Ukraine in 1944 –1959 years, factors of influence the formation of its content, we define its structure and function.
Keywords: content and structure of secondary education; the content; structure; format and function ofschool textbooks; principles and methods of teaching; scientific and methodical providing of educationalliterature